Effect of Stocking Density on Skeletal Development of Turkey Poults (Indian Journal of Animal Production and Management, 2024)
Stocking density is one of the important aspects of housing management. Increased stocking density  can influence the skeletal development of broilers negatively and can increase the leg abnormalities  thereby generating welfare issue for the same. To study the effect of stocking density, an experiment  was conducted at poultry farm, DUVASU, Mathura. Week old turkey poults were distributed randomly  on uniform body weight basis in three treatment groups- T-1: standard stocking density (2.5 ft2 per  bird); T-2: high stocking density (1.25 ft2 per bird) and T-3: low stocking density (5 ft2 per bird). Tibia  and femur were separated from the sacrificed birds and dried in oven at 1050C for 72 hours. There  after cooling down to room temperature, the bones were weighed. Digital radiographs of the bones  were taken. The dimensions and thickness of the bones were measured. Average femur length was  found to be significantly higher (p
Keywords: Turkey,; stocking density; femur; tibia